Linear response for temperature sensing achieved by implanting Er3+ into the grain boundary of transparent MgAlON ceramic. (1st July 2023) - Chen, Bowen; Wang, Bin; Jing, Zhengyang; Wang, Hao; Tu, Bingtian; Wang, Weimin; Fu, Zhengyi
Abstract: Fluorescence thermometry is considered one of the most perspective temperature sensing techniques. However, few materials reported could combine a wide operating temperature range with stable and high sensing sensitivity. Herein, the fluorescence thermometry based on MgAlON:0.01 at.% Er 3+ transparent ceramic was successfully proposed using the idea of local structural engineering, which distributed the Er 3+ uniformly into the grain boundary of MgAlON transparent ceramic. It is demonstrated that the special local environment of Er 3+ led to different fluorescence responses from those in crystalline or amorphous structures. Instead of the classic Boltzmann exponential relationship, a highly linear downshift fluorescence intensity ratio of thermally coupled energy levels of Er 3+ with temperature was exhibited. A novel and constant absolute sensitivity (0.0156 K −1 ) was obtained within the tested temperature range (300–573 K). This work reveals the significance of the local structure of the activators in the design of high-performance fluorescence temperature sensors. Graphical abstract: Image, graphical abstract